2013
DOI: 10.1242/dev.088567
|View full text |Cite
|
Sign up to set email alerts
|

Modular development of the teleost trunk along the dorsoventral axis and zic1/zic4 as selector genes in the dorsal module

Abstract: SUMMARYTeleost fish exhibit remarkable diversity in morphology, such as fins and coloration, particularly on the dorsal side. These structures are evolutionary adaptive because their back is highly visible to other individuals. However, owing to the late phenotypic appearance (from larva to adult) and lack of appropriate mutants, the genetic mechanisms that regulate these dorsoventrally asymmetric external patterns are largely unknown. To address this, we have analyzed the spontaneous medaka mutant Double anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(42 citation statements)
references
References 61 publications
2
40
0
Order By: Relevance
“…Given that HMD size correlates with transcriptional repression level, this HMD shortening might promote zic1/zic4 expression. To examine when this HMD shortening occurs during development, we additionally investigated the DNA methylation pattern in dorsal and ventral myotome at the hatching stage, a stage when the dorsal-specific expression of zic1/zic4 is already induced (Kawanishi et al, 2013). As expected, ChIP-qPCR revealed that the pattern of active and repressive histone modifications was already established in the dorsal and ventral myotome by the hatching stage ( Fig.…”
Section: Human-specific K27hmds Mark Genes Related To Neuronal Activimentioning
confidence: 71%
See 3 more Smart Citations
“…Given that HMD size correlates with transcriptional repression level, this HMD shortening might promote zic1/zic4 expression. To examine when this HMD shortening occurs during development, we additionally investigated the DNA methylation pattern in dorsal and ventral myotome at the hatching stage, a stage when the dorsal-specific expression of zic1/zic4 is already induced (Kawanishi et al, 2013). As expected, ChIP-qPCR revealed that the pattern of active and repressive histone modifications was already established in the dorsal and ventral myotome by the hatching stage ( Fig.…”
Section: Human-specific K27hmds Mark Genes Related To Neuronal Activimentioning
confidence: 71%
“…We focused on the zic1 and zic4 (zic1/zic4) genes because they have a particularly large K27HMD (26 kb) in medaka blastula embryos (Fig. 5A) and their function has been extensively studied in medaka (Kawanishi et al, 2013;Moriyama et al, 2012). zic1/ zic4, organized head-to-head with a small intergenic sequence (∼3.4 kb), encode zinc-finger transcription factors and function in the neuronal development and specification of dorsal fate in the trunk (Kawanishi et al, 2013;Merzdorf, 2007).…”
Section: Human-specific K27hmds Mark Genes Related To Neuronal Activimentioning
confidence: 99%
See 2 more Smart Citations
“…All of these five genes can act as transcription factors to affect early embryo development. For instances, Dmrta2 in mice is essential in the early development of the telencephalon via the formation of the cortical hem and maintaining of neural progenitors [39]; homeobox genes HOXA9 and HOXA7 spatially and temporally regulate morphogenesis and differentiation during embryonic development [40]; homeobox gene SIX3 provides necessary instructions for the formation of the forebrain and eye development [41]; ZIC4 has been proposed to regulate lateemerging characteristics in the dorsal surface with ZIC1 [42]. Due to their important roles in embryo development, methylation of these genes could affect important cellular functions and eventually promote tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%